The changes of Cain: violence and the lost brother in Cain and Abel literature - Quinones, Ricardo J. (Princeton legacy library, 1991)
Era by era, from the writings of the classical Christian epoch up to East of Eden and Amadeus, from Philo to Finnegans Wake, Ricardo Quinones examines the contexts of a master metaphor of our culture. This brilliant work is the first comprehensive book on the Cain and Abel story."Ricardo Quinones takes us on a grand tour of Western civilization in his admirable book, which reveals the riches of the Cain-Abel story as it develops from its Biblical origin to Citizen Kane and Michel Tournier. This is cultural history and literary criticism of the first order, finely written, formidably but gracefully erudite, and illustrating the capacity of Judeo-Christian culture and the modernity emerging from it constantly to criticize the darker side of its own foundations and realizations."--Joseph Frank"Ricardo J. Quinones skips Biblical and Talmudic exegesis to follow Cain and Abel through later centuries, from classical times to the present. What he uncovers sheds light on important shifts of consciousness and behavior in European and American culture. ... Quinones writes with true eloquence and conviction. . . ."--James Finn Cotter, The Hudson Review"Quinones's study of how [the] three Cains were transformed by Romanticism and Modernism into a sometimes positive, sometimes negative, but always necessary archetype of the modern world is literary and cultural analytic history at its very best."--ChoiceRicardo J. Quinones is Josephine Olp Weeks Professor of English and Comparative Literatures, and Director of the Gould Center for Humanistic Studies, at Claremont McKenna College in Claremont, California. He is the author of The Renaissance Discovery of Time (Harvard), Dante Alighieri (Twayne), and Mapping Literary Modernism: Time and Development (Princeton). Originally published in 1991. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905